Faber Polynomial Coefficient Bounds for m-Fold Symmetric Analytic and Bi-univalent Functions Involving q-Calculus. (26th October 2021) - Jia, Zeya; Khan, Shahid; Khan, Nazar; Khan, Bilal; Asif, Muhammad
Abstract : In our present investigation, by applying q -calculus operator theory, we define some new subclasses of m -fold symmetric analytic and bi-univalent functions in the open unit disk U = z ∈ ℂ : z < 1 and use the Faber polynomial expansion to find upper bounds of a m k + 1 and initial coefficient bounds for a m + 1 and a 2 m + 1 as well as Fekete-Szego inequalities for the functions belonging to newly defined subclasses. Also, we highlight some new and known corollaries of our main results.